CLASSROOM MANAGEMENT LEADERSHIP AND LEADERSHIP CONTRIBUTIONS TO CLASSROOM MANAGEMENT - İsa DAĞ (Fırat University, 2019)
In this study ; the definition of leadership, the leadership theories , the leadership of the teacher , the charecteristics of a leader teacher , the power supply of a leader teacher and the effects of the leader ship are described. To accompolish this goal,the study according to a literature scanning model is carried out. The human beings facing what is leadership have always been wonders about it. They have always investigatedwhy some people around them are more productive , more creative and moredaring than the others. In the absence ofscientific research period , they tried to find some mysticalexplanatin about it.Together with science thousands of research about leadership have been carried out. From past to present;many theorical explanations, changed in different ways, have been carried out. Still, no clarity is provided about it. Nowadays the role of leadership is one of the qualities which are added to the changing profile of the teachers. In this new educational approach; the model of leader teacher who can help the students, parents, neighbourhood and collegues in teaching and in